Alleles of unc‐33/CRMP exhibit defects during Caenorhabditis elegans epidermal morphogenesis. Issue 10 (25th May 2022) - Prins, Rachel; Windsor, Peter; Miller, Bill R.; Maiden, Stephanie
Abstract: Background: Microtubule‐associated proteins regulate the dynamics, organization, and function of microtubules, impacting a number of vital cellular processes. CRMPs have been shown to control microtubule assembly and axon outgrowth during neuronal differentiation. While many microtubule‐associated proteins have been linked to roles in cell division and neuronal development, it is still unclear the complement that control the formation of parallel microtubule arrays in epithelial cells. Results: Here we show through time‐lapse DIC microscopy that Caenorhabditis elegans embryos homozygous for the weak loss‐of‐function allele unc‐33(e204) progress more slowly through epidermal morphogenesis, while animals homozygous for strong loss‐of‐function alleles exhibit more embryonic lethality. Identification of two novel missense mutations in unc‐33(e572), Val476Gly, and Ser731Thr, lead to computational approaches to determine the potential effects of these changes on UNC‐33/CRMP structure. Molecular dynamics simulations show that for Asp389Asn and Arg502His, two other known missense mutations, local changes in protein‐protein hydrogen bonding affect the stability of the protein. However, the Val476Gly/Ser731Thr combination does not alter the structure or energetics of UNC‐33 drastically when compared to the wild‐type protein. Conclusions: These results support a novel role for UNC‐33/CRMP in C. elegans epidermal development and shed light on how individual amino acid changes cause a loss‐of‐function in UNC‐33. Key Findings: A weak loss‐of‐function unc‐33 allele is slow to complete epidermal morphogenesis. Strong loss‐of‐function unc‐33 alleles exhibit embryonic lethality. Certain UNC‐33 missense mutations are predicted to alter protein stability